2017
DOI: 10.1016/j.ccell.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa9 and Meis1 Cooperatively Induce Addiction to Syk Signaling by Suppressing miR-146a in Acute Myeloid Leukemia

Abstract: SummaryThe transcription factor Meis1 drives myeloid leukemogenesis in the context of Hox gene overexpression but is currently considered undruggable. We therefore investigated whether myeloid progenitor cells transformed by Hoxa9 and Meis1 become addicted to targetable signaling pathways. A comprehensive (phospho)proteomic analysis revealed that Meis1 increased Syk protein expression and activity. Syk upregulation occurs through a Meis1-dependent feedback loop. By dissecting this loop, we show that Syk is a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
90
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(96 citation statements)
references
References 83 publications
(111 reference statements)
6
90
0
Order By: Relevance
“…We further verified that ZNF205‐AS1 increased EGR4 mRNA stability, and therefore up‐regulated EGR4 expression. microRNAs (miRNAs) are well‐known to bind the 3’UTR of target mRNAs and induce the degradation and/or translation inhibition of target mRNAs . The interaction between ZNF205‐AS1 transcript and EGR4 mRNA 3’UTR may protect EGR4 mRNA from miRNAs‐induced degradation, which need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We further verified that ZNF205‐AS1 increased EGR4 mRNA stability, and therefore up‐regulated EGR4 expression. microRNAs (miRNAs) are well‐known to bind the 3’UTR of target mRNAs and induce the degradation and/or translation inhibition of target mRNAs . The interaction between ZNF205‐AS1 transcript and EGR4 mRNA 3’UTR may protect EGR4 mRNA from miRNAs‐induced degradation, which need further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Syk, a critical signaling mediator downstream of B cell antigen receptor, is another potential target through which miR-146a may impact B cell proliferation. Abrogation of miR-146a-mediated repression of SYK was recently implicated as a major driving factor in Hoxa9/Meis1-induced mouse model of myeloid leukemogenesis (38). Although this exact target interaction may not be applicable to human leukemias because of the lack of any miR-146a binding sites in the human Syk 3′UTR, it is illustrative of the potential role of miR-146a dysfunction in driving a variety of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…15 In AML, HoxA9 could suppress miR-146a and extend the survival ratio in leukaemia model. 22 To further strengthen the concept that HoxA9 regulates the malignancy of leukaemia through regulating microRNA expression level, this study searched for the potentially involved microRNAs and found that microRNA 663 and 494 are regulated by HoxA9 ( Figure 6). More importantly, this regulation is able to control leukaemia cell differentiation.…”
Section: Discussionmentioning
confidence: 99%